Livelihood diversification strategies, incomes and soil management strategies: a case study from Kerio Valley, Kenya - Iiyama, Miyuki; Kariuki, P.; Kristjanson, Patricia M.; Kaitibie, S.; Maitima, J. (Wiley, 2008)
African farmers diversify their livelihood strategies through on-farm and off-farm activities. We cluster households according to similar livelihood diversification strategies and explore the implications for income levels and sustainable soil management practices. Five main livelihood diversification strategies were being pursued. Households with off-farm income, and those pursuing higher return agricultural activities earned more than twice as much as the lowest income groups, which were the least diversified. They also were more likely to implement soil conservation measures. Policies aimed at improving household well-being need to take into account a wide range of household asset endowments and livelihood strategies being pursued.